Pengaruh Sosial Media Terhadap Berwirausaha Dikalangan Remaja Kabupaten Pasuruan: Maulidatul Masudha, Risma Rossidha, Khofidatus Soliha, Enik Sulistyowati - Maulidatul, Masudha; Khofidatus Soliha; Risma, Rossidha; Enik, Sulistyowati (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
In the digital age, social media is predominantly used by various groups, especially teenagers, mainly for entertainment and social connections. However, if viewed from a positive perspective, social media can also serve as a platform to create job opportunities for individuals. This study aims to examine whether social media influences the entrepreneurial interest of teenagers in Pasuruan district. A quantitative approach was employed, with data collected through questionnaires distributed to over 100 teenage respondents in the district. The study used correlation and significance analysis techniques. The findings indicate that social media (variable X) has a strong impact on teenagers' entrepreneurial interest (variable Y) in Pasuruan district. The results reveal a significant relationship, with a correlation value of 0.725 and a coefficient of determination of 0.525, meaning 52.5% of the variation in entrepreneurial interest can be explained by social media.